The effects of selected toxic elements on birth weight. The Norwegian Mother and Child contamination cohort study (MISA study) - Orin, Sadia Asad (UiT Norges arktiske universitet, 2018)
Background - Birth weight is an important indicator for predicting newborn baby’s health. Particular toxic elements: lead (Pb), arsenic (As), mercury (Hg), cadmium (Cd) have ability to cross the transplacental barrier and effect the fetal growth and development. These toxic elements exposure during pregnancy have been associated with negative birth outcomes like low birth weight (LBW). Objectives - The objective of this study was to conduct the assessment of selected toxic elements (Pb, Hg, As and Cd) in the mother’s blood sample during the gestational period and their effects on birth weight. Methods - A subset of 282 pregnant women who delivered their babies from the North Norwegian Mother-and-Child Study (MISA) was included in our study. The participants completed a detailed self-reported information questionnaire supplied by MISA study. Blood samples were collected during the 2nd trimester (P1) and 3rd postpartum (P2) in different regions of Northern Norway, and were analyzed for four selected toxic elements. Both univariate and multivariate analyses were conducted, birth weight was adjusted for a range of potential confounders. Results - In multivariable model, we revealed that an increasing maternal blood Pb concentration negatively influenced birth weight in baby girls (p-value=0.009). Moreover, elevated maternal blood Cd concentration increased the chances of reduced birth weight in baby boys (p-value=0.045) when adjusted for alone. We also found all the toxic elements peaked at P2 except Hg which is at the P1 time period. Conclusion - The present study found a significant inverse association between maternal Pb concentration and birth weight in female neonates only. The negative correlation of maternal Cd concentration with birth weight is observed in male neonates but not in female neonates. These significant correlations confirm the potential for sex response differences to Pb and Cd exposure.